Reporting the parliament : a Nigerian case study - Ohaja, Edith; Nwankpa , Nduka; Amadin , Ruth (Brazilian journalism research, 2022)
ABSTRACT – The study investigated, using content analysis, the patterns of reportage of Nigeria’s Akwa Ibom State House of Assembly by Comfort 95.1 FM, Planet 101.5 FM, and Inspiration 105.9 FM between 2018 and 2019. Results showed similarities/divergences in the news coverage and reportage approach of the stations. Budget/bills/public hearings and motions dominated the news focus. Critical analysis in reportage of the House was almost non-existent. No clear case of media agenda-setting was established, as there was little or zero influence the media had on directing the course of the Assembly. Rather, the media’s focus was determined by the steps of the lawmakers. It was recommended that a weekly magazine program dedicated to the activities of the Assembly be adopted by each radio station. This would help incorporate information that a timed-news bulletin cannot accommodate and fan the flame of investigative journalism and critical analysis of the activities of the Assembly. RESUMO – O estudo investigou, por meio da análise de conteúdo, os padrões de reportagem da Assembleia Estadual Akwa Ibom da Nigéria por Comfort 95.1 FM, Planet 101.5 FM e Inspiration 105.9 FM, entre 2018 e 2019. Os resultados mostraram semelhanças/divergências na cobertura jornalística e na abordagem da reportagem das estações. Orçamento/projetos/audiências públicas e moções dominaram o foco das notícias. A análise crítica na reportagem da Câmara foi quase inexistente. Não foi estabelecido nenhum caso claro de definição da agenda da mídia, pois havia pouca ou nenhuma influência da mídia na direção do curso da Assembleia. Em vez disso, o foco da mídia foi determinado pelos passos dos legisladores. Foi recomendado que cada estação de rádio adotasse um programa de revista semanal dedicado às atividades da Assembleia. Isso ajudaria a incorporar informações que um boletim de notícias cronometrado não pode acomodar e atiçar a chama do jornalismo investigativo e da análise crítica das atividades da Assembleia. RESUMEN – El estudio investigó, mediante análisis de contenido, los patrones de reportaje de la Asamblea Estatal de Akwa Ibom de Nigeria por parte de Comfort 95.1 FM, Planet 101.5 FM e Inspiration 105.9 FM entre 2018 y 2019. Los resultados mostraron similitudes/divergencias en la cobertura de noticias y el enfoque de reportaje de las estaciones. Presupuesto/proyectos de ley/audiencias públicas y mociones dominaron el foco de las noticias. El análisis crítico en el reportaje de la Cámara era casi inexistente. No se estableció un caso claro de establecimiento de la agenda de los medios, ya que hubo poca o ninguna influencia de los medios en la dirección del curso de la Asamblea. Más bien, el enfoque de los medios estuvo determinado por los pasos de los legisladores. Se recomendó que cada emisora ​​de radio adoptara un programa semanal dedicado a las actividades de la Asamblea. Esto ayudaría a incorporar información que un noticiero programado no puede acomodar y avivaría la llama del periodismo de investigación y el análisis crítico de las actividades de la Asamblea.